Sustainable Water Management in Eco-Tourism: Addressing Water Scarcity in Morocco’s Northern Piedmont of the Western High Atlas - Ait Zamzami, Hamza; Elaanzouli, Mohammed; Zahrani, Ayoub; Ezzardi, Abdelghani; Saidi, Jamila; Mounaji, Jamal; Belhaj, Siham; Ammari, Abdelmalek; Jumadi, Jumadi; Boumeaza, Taieb (Eco-Tourism and Sustainable Development, 2025)
The northern piedmont of Morocco’s western High Atlas is grappling with significant environmental challenges, particularly regarding the availability of water. The region, characterized by its semi-arid climate, is facing increasing pressure from expanding tourism development, which exacerbates the already strained water resources. While tourism is often seen as a sustainable economic driver, its rapid growth has led to a surge in water demand, further complicating resource management. This study investigates the spatial and temporal tensions between tourism development and water resource preservation in this delicate region. By employing a combination of territorial systems analysis, field surveys, and Geographic Information Systems (GIS), the research evaluates water consumption across a range of tourism accommodations, including hotels, gîtes, and resorts. The findings reveal significant disparities in water use, with large tourist complexes and villas accounting for over 83% of the total water consumption. In response to these challenges, the study recommends strategies such as the implementation of circular water economies, improving water-use efficiency in tourism facilities, and fostering stronger local governance and regulation. Integrating water conservation measures into tourism planning and management is crucial to balancing economic growth with the environmental limitations of the region. This research provides valuable insights and practical recommendations for managing tourism sustainably in water-scarce areas, offering a framework for balancing development with environmental sustainability.